Hidden transition in multiferroic and magnetodielectric CuCrO2 evidenced by ac-susceptibility. (23rd June 2017) - Shukla, Kaushak K.; Pal, Arkadeb; Singh, Abhishek; Singh, Rahul; Saha, J.; Sinha, A. K.; Ghosh, A. K.; Patnaik, S.; Awasthi, A. M.; Chatterjee, Sandip
Abstract: Ferroelectric polarization, magnetic-field dependence of the dielectric constant and ac and dc magnetizations of frustrated CuCrO2 have been measured. A new spin freezing transition below 32 K is observed which is thermally driven. The nature of the spin freezing is to be a single-ion process. Dilution by the replacements of Cr ions by magnetic Mn ions showed suppression of the spin freezing transition suggesting it to be fundamentally a single-ion freezing process. The observed freezing, which is seemingly associated to geometrical spin frustration, represents a novel form of magnetic glassy behavior.